PROGRESS: the PROMISE governance framework to decrease coercion in mental healthcare. Issue 3 (16th July 2018) - Lombardo, Chiara; Van Bortel, Tine; Wagner, Adam P; Kaminskiy, Emma; Wilson, Ceri; Krishnamoorthy, Theeba; Rae, Sarah; Rouse, Lorna; Jones, Peter Brian; Kar Ray, Manaan
Abstract : Reducing physical intervention in mental health inpatient care is a global priority. It is extremely distressing both to patients and staff. PROactive Management of Integrated Services and Environments (PROMISE) was developed within Cambridgeshire and Peterborough NHS Foundation Trust (CPFT) to bring about culture change to decrease coercion in care. This study evaluates the changes in physical intervention numbers and patient experience metrics and proposes an easy-to-adopt and adapt governance framework for complex interventions. PROMISE was based on three core values of: providing a caring response to all distress; courage to challenge the status quo; and coproduction of novel solutions. It sought to transform daily front-line interactions related to risk-based restrictive practice that often leads to physical interventions. PROactive Governance of Recovery Settings and Services, a five-step governance framework (Report, Reflect, Review, Rethink and Refresh), was developed in an iterative and organic fashion to oversee the improvement journey and effectively translate information into knowledge, learning and actions. Overall physical interventions reduced from 328 to 241and210 across consecutive years (2014, 2015–2016 and 2016–2017, respectively). Indeed, the 2016–2017 total would have been further reduced to 126 were it not for the perceived substantial care needs of one patient. Prone restraints reduced from 82 to 32 (2015–2016 and 2016–2017, respectively). During 2016–2017, each ward had a continuous 3-month period of no restraints and 4 months without prone restrains. Patient experience surveys (n=4591) for 2014–2017 rated overall satisfaction with care at 87%. CPFT reported fewer physical interventions and maintained high patient experience scores when using a five-pronged governance approach. It has a summative function to define where a team or an organisation is relative to goals and is formative in setting up the next steps relating to action, learning and future planning.